Managing Native Hip Protrusio: Simplified Classification and Surgical Recommendations - Lidia Ani; Zachary Radford; Lee E. Rubin (Osteology, 2023)
Protrusio acetabuli is a unique osteological condition that has been long described in the literature and is known to potentially increase both the surgical complexity and the risk of complications when performing total hip arthroplasty. Although grading systems for native hip protrusio have been described in the past, there has not yet been a widely adopted classification system that categorizes the condition into separate classes in order to guide management. We propose a novel classification system with the goal of simplifying and standardizing the management of protrusio acetabuli in the context of modern total hip arthroplasty. This classification system describes protrusio based on the relationship of the femoral head to the ilioischial and iliopectineal lines, allowing for a more reproducible and consistent categorization of pathology. We also discuss general recommendations and technical pearls for total hip arthroplasty in the protrusio patient population, including the use of strategic soft tissue releases, fluoroscopy, navigation, bone graft, and augments.